Technical report: bookstore selection by using Fuzzy TOPSIS / Riza Hazmahanim Johari, Nur Farahanim Mohd Fadzir and Nur Hidayah Zulkifli - Johari, Riza Hazmahanim; Mohd Fadzir, Nur Farahanim; Zulkifli, Nur Hidayah (2016)
Nowadays, in every business management, supplier selection is an important issue in order to select the right supplier that can reduce cost and time. Deciding the best supplier is complicated for Mathematics' lecturer because it is involving qualitative and quantitative criteria that should be considered. In this study, the Fuzzy TOPSIS is applied to select the better supplier when lecturer as a decision maker set the target value for each criterion. The criteria selected in this study are price, quality, delivery and warranty and the alternative is BNS Supply Trading, Delima Ilmu Enterprise and ABA Bookstore. Linguistic term described the rating of each alternative and the weight of each criterion that can be expressed in triangular fuzzy numbers. The distance is calculated between two triangular Fuzzy numbers. In this study, closeness coefficient is used to identify the ranking order of all alternatives by calculating the distance to both the Fuzzy Positive Ideal Solution (FPIS) and Fuzzy Negative Ideal Solution (FNIS). The result shows that Delima Ilmu is the best supplier because have the highest closeness coefficient values.